Ковель за часів князя Андрія Курбського - Bortnikova, Alla; Бортнікова, Алла (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Здійснено аналіз організації управління й самоврядування в Ковелі за часів князя Андрія Михайловича Курбського (1564–1583 рр.). Показано становище міста під час передачі його у володіння та управління Курб-ському на ленному праві. Простежується розвиток торгівлі й ремісництва, участь у них ковельських міщан. Схарактеризовано діяльність намісників князя та міських посадовців.The article analysis of the organization and selfgovernment in Kovel in the time of Prince Andrei's Kurbskii (1564-1583). It was showing the status of the city at the time of its transfer to the ownership and management of Kurbski on feudal law that provided for by the law GDL par with the nobility performance by Prince and the County of military conscription obligations of public servants. It was showing the activity of the governors of the prince, which he generously distributed ownership in Kovel parish.
Kovel During Prince Andrei’s Kurbski
Keywords: Велике князівство Литовське; Польська Корона; Волинська земля; привілей; князь; староста; Grand Duchy of Lithuania; the Polish Crown; Volyn land; Privilege; Prince; Mayor